The association between personality traits and readiness to change among working adults in service sector: Organizational commitment as a mediator - Shum, Pui Lam (2023)
Organizational change is a common process for organizations to meet market requirements, drive profitability, and ensure sustainability. However, the failure rate of change initiatives can be as high as 70% or more. Employees’ readiness to adopt change are crucial as they are the foundation of organizational operations. Therefore, it is essential to identify the dispositional variables that can improve this phenomenon. The present study examined the influence of personality traits on employees' readiness for organizational change. Additionally, it explored the mediating role of organizational commitment in the relationship between personality traits and readiness to change. Data was collected from 462 participants using snowballing and purposive sampling methods. Participants were employees with a minimum of one year of experience in private limited companies within the service sector in Kuala Lumpur. The analysis employed the Pearson correlation technique as a prerequisite for multiple regression analysis. Subsequently, multiple regression analysis was conducted to investigate the effects of five personality traits on readiness to change. Mediation analysis was also utilized to explore the mediating role of organizational commitment in the relationship between iii personality traits and employees' readiness to change. The findings indicated that employees with high expression of agreeableness, emotional stability, openness to experience, and organizational commitment are more likely to be ready for organizational change. Furthermore, organizational commitment significantly mediated the relationship between personality traits (specifically agreeableness and conscientiousness) and readiness to change. In conclusion, this study offers valuable implications for employees and employers in the service sector of Kuala Lumpur regarding readiness for organizational change. Employees can benefit from understanding their personality traits and organizational commitment to assess their readiness and develop necessary adaptation skills. Employers can leverage assessments of employees' personality traits and commitment levels during the hiring process, predict their readiness for organizational change, and implement targeted training programs. By fostering a culture that values flexibility and change receptiveness, employers can create an environment conducive to successful organizational transitions in the service sector.